Studi Fluiditas Aluminium Minuman Kaleng Cair Dengan Variasi Temperatur Tuang Dan Ketebalan Rongga - Andri Andri; Dedy Masnur (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Pekanbaru has a potential to produce scrap of aluminum beverage cans, it is estimated about 4.5 tons per month in each collectors. Recycling of aluminum cans is still limited to transforming the cans into ingots, to produce an efficient product desing fluidity test as needed. to be examined on fluidity. Qudong method 1999, used in this research with varying pouring temperature; 650oC, 700oC, 750oC, die temperature; 100oC, 200oC, 300oC and cavity thickness; 0.5 mm, 1.0 mm, 1.5 mm, 2.0 mm, 2.5 mm, 3.0 mm, 3.5 mm, 4.0 mm. Fluidity increased with the increasing pouring temperature, with 55.77% at temperature 650oC-700oC and 72.75% at temperature 700oC-750oC. Fluidity increases with cavity thickness, maximum fluidity achieved at temperature 750oC at 4.0 mm with a length of 120 mm and minimum fluidity can be filled with molten metal is at 1.5 mm with a length of 2.67 mm.Keywords: fluidity, molten aluminum cans, pour temperature, cavity thickness.